2019
DOI: 10.4314/aja.v8i2.189031
|View full text |Cite|
|
Sign up to set email alerts
|

Morphometric study of cephalo-facial indices among Bini children in southern Nigeria

Abstract: Cephalometry is an important branch of anthropometry which involves the morphological study of structures present in the human head or scientific measurement of the dimensions of the head. Some of the most important cephalometric parameters include the length/height and breadth/width of the head, the face and the nose as well as their respective indices. These cephalometric parameters are vital in the description of variation which is a common phenomenon that characterizes human physiognomy. They are also usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…This also agrees with many studies conducted in our locality (Omotoso et al, 2019;Udo-Affah et al, 2021) and across the globe at large, however, among healthy subjects (Omotoso et al, 2019;Paulinus et al, 2019). Unlike in many studies (Golalipour et al, 2005;Fawehinmi et al, 2009;Bernhardt et al, 2017), which were conducted on healthy subjects, the present study was among stroke patients and there was no similar study found or done in this locality, where stroke patients' head types were assessed, however, the findings of the present study agree with the studies mentioned above (Omotoso et al, 2019;Udo-Affah et al, 2021). Like in many other studies (Ilayperuma, 2011;Maina et al, 2011;Terkula et al, 2019), conducted on healthy individuals, sexual dimorphisms were observed in FOD and BPD.…”
Section: Discussionsupporting
confidence: 94%
“…This also agrees with many studies conducted in our locality (Omotoso et al, 2019;Udo-Affah et al, 2021) and across the globe at large, however, among healthy subjects (Omotoso et al, 2019;Paulinus et al, 2019). Unlike in many studies (Golalipour et al, 2005;Fawehinmi et al, 2009;Bernhardt et al, 2017), which were conducted on healthy subjects, the present study was among stroke patients and there was no similar study found or done in this locality, where stroke patients' head types were assessed, however, the findings of the present study agree with the studies mentioned above (Omotoso et al, 2019;Udo-Affah et al, 2021). Like in many other studies (Ilayperuma, 2011;Maina et al, 2011;Terkula et al, 2019), conducted on healthy individuals, sexual dimorphisms were observed in FOD and BPD.…”
Section: Discussionsupporting
confidence: 94%
“…Palagiri et al 2 in 2020 they done by their study of Kadapa Population the average value of facial Index was 83.04 in males & 80.0 in females. Omotoso et al 3 they found that in 450 subjects (235 males & 235 females) the mean facial Index was more in males as compared to females between ages 5-12 years. The mesoproscopic face type was the most prevalent face type among both male (62.6%) and female (47.4%) in Nigerian.…”
Section: Discussionmentioning
confidence: 96%
“…In case of natural disasters like Earthquake, Landslides and in diverse injury like aircraft crash, railway and road traffic, anthropometry helps in identification of the deceased person. [3] Facial anthropometry plays an important role in the identification in treatment planning, evaluation and outcome assessment in several health disciplines of an individual especially in forensic pathology, cosmetic surgery, Aesthetics, surgery of the maxilla (upper jaw) and face, etc. Face is the main part of the body which is provides high importance in disclosing identity of a person.…”
Section: Introductionmentioning
confidence: 99%
“…In forensics and physical anthropology, the study of nasal anthropology is crucial since it is one of the methods that could beused to identify an individual's race, ethnicity, and gender. It is the opinion of several researchers that race, sex, age, and environmental factors along with biological factors have impact on body dimensions, particularly in the head and neck regions [3][4][5] . In anthropology and forensic medicine, the knowledge of nasal index (NI) could be in determining race, ethnicity and sex of individuals whose identity is not known 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A rhinoplastic surgeon must make adjustments to the nose's size or shape to get the desired aesthetic result. Additionally, the rhinoplastic surgeon can alter a patient's nose without jeopardizing the patient's wish to keep his beauty status by performing a nasal analysis of that patient's unique ethnic group 5 . Measuring the nasal index in healthy individuals helps dysmorphologists make an early diagnosis of various dysmorphic conditions including cleft lip and palate 1 .…”
Section: Introductionmentioning
confidence: 99%